Use of Solar Drier Papapya Lather as a Fat Replacer in Cakes - Ansari, Anam; Aghar, Ali; Shahid, Muhammad; Tanweer, Saira (Journal of Food Technology Research, 2014)
Fat is a major constituent of food that softens the food product in addition to provide energy. High fat foods are energy dense foods that produce obesity and also some other major disorders. To reduce the risk of disease fat replacers can be used. Weight conscious people are adopting these fat replacers very quickly. There are three different types of fat replacers i.e. carbohydrate based, protein based and fat based. Solar dried papaya lather is an excellent source of fat replacers. This fat replacer can be used in baked especially for cakes products instead of shortening and oil. Papaya lather has the same functions as of fats. It has numerous theraputical perspectives and can be used in different drugs preparation. Papaya is a rich source of papain that acts as meat tenderizer. Papaya fruit has rich contents of antioxidant activity hence important to be used in diet owing to different health benefits.